2004
DOI: 10.1016/j.accreview.2004.10.068
|View full text |Cite
|
Sign up to set email alerts
|

Association of atrial fibrillation and obstructive sleep apnea

Abstract: Background-Obstructive sleep apnea (OSA) is associated with recurrent atrial fibrillation (AF) after electrocardioversion.OSA is highly prevalent in patients who are male, obese, and/or hypertensive, but its prevalence in patients with AF is unknown. Methods and Results-We prospectively studied consecutive patients undergoing electrocardioversion for AF (nϭ151) and consecutive patients without past or current AF referred to a general cardiology practice (nϭ312). OSA was diagnosed with the Berlin questionnaire,… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

5
213
3
19

Year Published

2006
2006
2020
2020

Publication Types

Select...
9

Relationship

0
9

Authors

Journals

citations
Cited by 178 publications
(240 citation statements)
references
References 25 publications
5
213
3
19
Order By: Relevance
“…Taken together, there is a possibility that IHR can be a potential risk factor of aortic dissection through the development of atherosclerosis. Although OSA is known to be an independent risk factor of several cardiovascular diseases such as heart failure, hypertension, ischemic heart disease, left ventricular dysfunction and arrhythmia [7][8][9][10][11][12][13][14][15], only few reports showed the association between OSA and aortic diseases such as aortic dilatation [20,26,27] and aortic dissection [16]. Serizawa et al [20] reported the trend towards larger ascending aortic diameter in 150 Japanese patients with OSA.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…Taken together, there is a possibility that IHR can be a potential risk factor of aortic dissection through the development of atherosclerosis. Although OSA is known to be an independent risk factor of several cardiovascular diseases such as heart failure, hypertension, ischemic heart disease, left ventricular dysfunction and arrhythmia [7][8][9][10][11][12][13][14][15], only few reports showed the association between OSA and aortic diseases such as aortic dilatation [20,26,27] and aortic dissection [16]. Serizawa et al [20] reported the trend towards larger ascending aortic diameter in 150 Japanese patients with OSA.…”
Section: Discussionmentioning
confidence: 99%
“…There is now substantial evidence of the relationship between obstructive sleep apnea (OSA) and cardiovascular diseases, such as heart failure, hypertension, ischemic heart disease, left ventricular dysfunction, and arrhythmia [7][8][9][10][11][12][13][14][15]. However, the association between aortic dissection and OSA was not fully investigated.…”
Section: Introductionmentioning
confidence: 99%
“…So ist gezeigt worden, dass Vorhofflimmern nach primär erfolgreicher elektrischer Kardioversion häufiger rezidiviert, wenn eine OSA besteht [7]. Des Weiteren weisen unselektierte Patienten mit Vorhofflimmern in einem hohen Prozentsatz (bis zu 50%) eine SBAS im Sinne einer OSA auf [8]. Schließlich konnte anhand einer Fallstudie gezeigt werden, dass die OSA Episoden von Vorhofflimmern triggern kann [9].…”
Section: Nächtliche Herzrhythmusstörungenunclassified
“…Bei Patienten mit arterieller Hypertonie konnte eine Prävalenz an obstruktiven Schlafapnoesyndromen (OSA) von 50% [12], bei Patienten mit KHK eine Präva-lenz von 33% [23] und bei Patienten mit Vorhofflimmern eine Prävalenz von 33-50% [7,15] gezeigt werden. Demgegenüber treten zentrale Schlafapnoesyndrome (CSA) v. a. bei Patienten mit Herzinsuffizienz auf.…”
unclassified